2020
DOI: 10.3390/sym12091450
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Viscous Dissipation and Brownian motion on Jeffrey Nanofluid Flow over an Unsteady Stretching Surface with Thermophoresis

Abstract: The goal of this investigation is to explore the influence of viscous dissipation and Brownian motion on Jeffrey nanofluid flow over an unsteady moving surface with thermophoresis and mixed convection. Zero mass flux is also addressed at the surface such that the nanoparticles fraction of maintains itself on huge obstruction. An aiding transformation is adopted to renovate the governing equations into a set of partial differential equations which is solved using a new fourth-order finite difference continuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Recently viscous dissipative fluid along with thermal radiation on MHD free convective flow was explored by Kishan and Deepa, 11 Pal and Mandal, 12 and Murthy et al 13 In these investigations, spanwise cosinusoidally fluctuating is not considered. El‐Zahar et al 14 discussed viscous dissipation as well as thermophoresis and Brownian motion effects on Jeffrey Nanofluid flow over an unsteady stretch surface. Hossam et al 15 reported the consequence of viscous dissipation along with ohmic heating on the MHD bio‐convection flow of a nanofluid enclosing gyrotactic microorganisms over an upright isothermal cone.…”
Section: Introductionmentioning
confidence: 99%
“…Recently viscous dissipative fluid along with thermal radiation on MHD free convective flow was explored by Kishan and Deepa, 11 Pal and Mandal, 12 and Murthy et al 13 In these investigations, spanwise cosinusoidally fluctuating is not considered. El‐Zahar et al 14 discussed viscous dissipation as well as thermophoresis and Brownian motion effects on Jeffrey Nanofluid flow over an unsteady stretch surface. Hossam et al 15 reported the consequence of viscous dissipation along with ohmic heating on the MHD bio‐convection flow of a nanofluid enclosing gyrotactic microorganisms over an upright isothermal cone.…”
Section: Introductionmentioning
confidence: 99%
“…El-Zahar ER, et al [6] Examined the influence of viscous dissipation and Brownian motion on Jeffrey nanofluid over an unsteady moving surface with thermophoresis and mixed convection where graphical outcomes indicated that augmentation buoyance ratio and thermophoresis parameter led to diminished velocity curves and increased temperature curve.…”
Section: Introductionmentioning
confidence: 99%
“…Irfan and Farooq 16 analyzed the magnetohydrodynamics (MHD) heat transfer of nanofluid flow over an exponentially stretching surface, including varying fluid characteristics. Other related studies scrutinizing nanofluids can be inspected in the following attempts 17–26 …”
Section: Introductionmentioning
confidence: 99%